Transforming Rural Communities through IoT: Socio-Digital Challenges and Opportunities in Afghan Agriculture - Azizi, Abdullah; Himmat, Bilal; Danish, Jawad (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study investigates the challenges and opportunities associated with implementing Internet of Things (IoT) technologies in Afghanistan's agricultural sector. Using a mixed methods approach comprising surveys, interviews, and focus group discussions with 200 participants across various regions the research assesses awareness, adoption, and perceived value of IoT among Afghan farmers. Findings show that while 60% of respondents were aware of IoT, only 30% had adopted such technologies. Key barriers include inadequate infrastructure, high costs, and limited technical expertise. Social factors—such as digital illiteracy and unequal access to technology—further restrict uptake, especially in marginalized rural communities. Despite these constraints, significant opportunities exist in areas like smart irrigation, crop health monitoring, and data-driven farming. These technologies hold promises for enhancing efficiency and sustainability while promoting digital inclusion and reducing regional disparities. The study underscores the need for targeted investment in infrastructure, training, and awareness to enable broader adoption. Its insights are critical for policymakers and stakeholders seeking to advance inclusive, technology-driven agricultural development in Afghanistan.